Broken Pears: A Reading of Samuel Bak’s Art - Garcia, Elenita (Silliman Journal, 2022)
This paper tries to show that, although Bak’s art is rooted in his experiences of the Holocaust, it extends them by pointing the spectator to a kind of reconciliation with the constant disintegration of the world that has been “wounded by the Holocaust.” As noticed by interpreters of his works, instead of painting a more direct representation of the Holocaust, Bak uses (iconic) symbols. This is the reason that Bak’s works can reach out to something more universal and is not completely tied down to the specific event of the Holocaust. His paintings have shown the world crumbling, decaying, and falling apart—apt illustrations of the Zen practice of realizing the world as devolving into original nothingness. Yet, it has also hinted at some hope, not in portraying the world becoming better than it is but by questioning assumptions about it and by blurring binary oppositions in one’s perceptions about the world. In this way, Bak joins the Zen masters in their practice of active engagement in the world while training the mind to see the world as it is.